2014
DOI: 10.1007/s11010-014-2248-3
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid mitigates the DMBA/croton oil-induced skin cancer progression in mice

Abstract: Skin cancer is the most common malignancy in the world and also one of the major causes of death worldwide. The toxic environmental pollutant 7,12-dimethylbenz[a]anthracene (DMBA) is a skin-specific carcinogen. Tannic acid (TA) is reported to be effective against various types of chemical-induced toxicities and carcinogenesis as well. In the present study, we have evaluated the therapeutic potential of tannic acid in DMBA + croton oil-induced skin cancer in Swiss albino mice. Protective effect of TA against sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Among which tannic acid, is a well-known polyphenol compound present in most of the fruits, vegetables, and plants, is reported to have potent anti-inflammatory, antioxidant, antimicrobial, antimutagenic and anticarcinogenic activities. Previous studies reported that tannic acid has promising clinical results against skin cancer [23], myocardial infarction [24], renal failure [25], hepatotoxicity/genotoxicity [26], diabetes [27] and Alzheimer disease [28]. Furthermore, tannic acid inhibited inflammatory cytokines and proinflammatory factors such as iNOS and COX2 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Among which tannic acid, is a well-known polyphenol compound present in most of the fruits, vegetables, and plants, is reported to have potent anti-inflammatory, antioxidant, antimicrobial, antimutagenic and anticarcinogenic activities. Previous studies reported that tannic acid has promising clinical results against skin cancer [23], myocardial infarction [24], renal failure [25], hepatotoxicity/genotoxicity [26], diabetes [27] and Alzheimer disease [28]. Furthermore, tannic acid inhibited inflammatory cytokines and proinflammatory factors such as iNOS and COX2 [25].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, anti-promotional activity of TA in the mouse skin through the reduction of oxidative stress as well as COX-2, iNOS, PCNA (proliferating cell nuclear antigen) protein, and proinflammatory cytokine such as IL-6 release was confirmed [23]. Anti-inflammatory activity of TA was also shown in the context of house dust mite-induced atopic dermatitis.…”
Section: Chemosenstization and Impact On Multidrug Resistancementioning
confidence: 87%
“…The anticarcinogenic potential of the crude venom extract obtained from L. quinquestriatus was evaluated using the classic DMBA/12- O -tetradecanoylphorbol-13-acetate or croton oil-induced two-stage mouse skin carcinogenesis model. 25 , 26 Animals were divided into five groups of 13 animals each. The dorsal skin of each animal was shaved with an electric clipper 2 days prior to initiation of the experiment.…”
Section: Methodsmentioning
confidence: 99%